Strategic Management for Strengthening the Competitiveness of State Islamic Elementary School in Lampung - Sopian, RM; Suharto, Suharto; Anshori, M. Afif (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze strategic management in strengthening the competitiveness of State Islamic Elementary Schools in Lampung Province, focusing on MIN 1 Bandar Lampung, MIN 1 South Lampung, and MIN 3 Bandar Lampung. It examines principals' leadership strategies, learning innovation, and human resource development as key factors in improving institutional competitiveness. In addition, this study seeks to develop a contextual and sustainable strategic management model based on Islamic educational values ​​and national madrasah education policies. This study uses a qualitative multi-site field research design conducted at MIN 1 Bandar Lampung, MIN 1 Lampung Selatan, and MIN 3 Bandar Lampung. Madrasah principals served as the main informants, supported by vice principals, teachers, administrative staff, school committee members, and parents selected through purposive sampling. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation and member checking to strengthen the credibility of the findings. The findings indicate that principals implement vision-based strategic planning, quality culture strengthening, and participatory decision-making. Learning innovation is carried out through technology integration, character education reinforcement, and creative learning models. Human resource development is conducted through continuous training, academic supervision, and professional competency improvement. Supporting factors include leadership commitment, stakeholder collaboration, and a conducive work culture, while constraints involve limited facilities and resistance to change. In conclusion, integrated strategic leadership management combined with learning innovation and human resource development significantly enhances the competitiveness of State Islamic Elementary Schools in Lampung Province.